Going through the motions: natural science and movement in Samuel Beckett's trilogy. Issue 11 (2nd November 2022) - Armstrong, Patrick
ABSTRACT: This article argues that scientific language and theory, combined with Samuel Beckett's study of philosophy, helps to shape the representations of movement patterns in his post-war trilogy of novels. Taking its cue from Beckett's engagement with scientific writing in the late 1920s and early 1930s, this article explores the physical and imperceptible forces that complicate the movements of characters in his prose fiction. The advances in quantum physics, which resonated with Beckett's attraction to both ancient atomism and the seventeenth-century 'Natural Science Period' of philosophy, inform his prose style and structural principles. By making use of newly available material, including archival research, I show that the terminology of natural science frequently reverberates through his writing, especially in his peculiar descriptions of moving bodies. I suggest that, for Beckett, the artistic process becomes a contraction, reducing motion to its fundamental terms in an attempt to understand the processes that underpin it. Movement, nonetheless, remains unpredictable, ceaseless, and technically difficult to represent.